Smoking and lung functions in sportsmen. Issue 2 (June 1988) - De, A K; Tripathi, M M
Abstract : Ten smoker sportsmen and 17 non-smoker sportsmen and 41 smoker non-sportsmen were studied. Lung function was assessed by means of Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV1), the ratio of FEV1 to FVC (FEV1%) and Peak Expiratory Flow Rate (PEFR). For the smokers, all the tests were conducted before smoking (BS) and 30 min after smoking (AS) two cigarettes consecutively to observe the acute effect of smoking. In the smoker sportsmen there was no significant difference between BS and AS measures of lung function. Before smoking smoker sportsmen had lower values for FEV1, FEV1% and PEFR than non-smoker sportsmen (p less than 0.05). However, smoker sportsmen show higher BS values of FEV1 (p less than 0.01), FEV1% (p less than 0.01) and PEFR (p less than 0.05) compared with those of smoker non-sportsmen who had similar smoking indices. These results indicated that the smoker sportsmen, despite exhibiting some degree of lung function impairment in relation to non-smoker sportsmen, still maintained rather better lung function status than the smoker non-sportsmen.